(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Various studies mentioned above show that social media platform can have impact on brand recognition and also make purchase intention to costumer to buy product through social media official. And using electronic service quality (E-SQ) can retain online costumers. The objectives of this study are (1) to find out the is marketing communication influence to consumer satisfaction; (2) to find out the is e-service quality influence to consumer satisfaction, and (3) to find out the find out the is marketing communication and e-service quality influence to consumer satisfaction together. This research using quantitative methode to describe the conclusion which the researcher distributes questionnaires in seven districts on South Tangerang, Banten.The population are student of Senior High School in South Tangerang area and sampling using Slovin methode with Margin of Error (MOE) was set in 5%. The data obtained comes from the results of the questionnaire and then calculated by software SPSS 25.0. The conclusion from data is both variable X1 (marketing communication) and variable X2 (e-service quality) have a positive effect on user satisfaction of rumah belajar service